THE ROLE OF FINANCIAL LITERACY AND ACCESS TO FINANCE IN DRIVING MSME GROWTH IN THE DIGITAL ERA - Prathama, Baiq Desthania; Nursansiwi, Dwi Arini; Armiani, Armiani (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The growth of Micro, Small and Medium Enterprises (MSMEs) in the digital era is greatly influenced by financial literacy and access to financing. However, many MSMEs face challenges in understanding financial management amidst digital transformation. This research aims to identify the dimensions of financial literacy that are most critical for the sustainability and growth of MSMEs in the digital era. Using a Systematic Literature Review (SLR) approach with the PRISMA framework, this research analyzes 60 relevant scientific articles from the Scopus, Web of Science, and Springer databases, published between 2017 and 2024. The findings show five main dimensions of financial literacy that have a significant influence on MSME performance, namely basic financial knowledge, digital financial skills, ability to adopt technology, financial risk management, and strategic financial planning. This research makes an important contribution to the development of financial literacy theory by integrating digital aspects, as well as offering practical guidance for governments and financial institutions in designing more effective financial literacy programs for MSMEs.